IMPACTJOINT STOCK COMPANIESON LOCAL LABOR MARKET (Research Bulletins of the Faculty of Economic Sciences, 2021)
This studywas devoted topublic companies, which form the linkof economic change,mainly because ofits capabilitiesdevelopment, employmentand the scopeof activities. The purpose of thispaper is toshow the role ofjoint-stock companieson the locallabor market.The present workdemonstrateslimited companiesfrom the perspec-tive ofcompetitiveness, andas individualsaffect theshape ofthe labor market.
Keywords: labor market, joint-stock company, employment, Pearson's correlation coef-ficient